2015
DOI: 10.1097/scs.0000000000001503
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aminoguanidine, Methylprednisolone, and Melatonin on Nerve Recovery in Peripheral Facial Nerve Neurorrhaphy

Abstract: Aminoguanidine and melatonin alone achieved an increase in regeneration after peripheral facial nerve neurorrhaphy, but methylprednisolone did not. The best healing was determined in the AG group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…In a study conducted by Karlidag et al [30], the facial nerves of 30 rabbits were resected, the free ends were anastomosed, and the effects of methylprednisolone and aminoguanidine on facial nerve regeneration were studied. The study showed that methylprednisolone had no beneficial effect in nerve regeneration, even increased degeneration [2,11,30].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In a study conducted by Karlidag et al [30], the facial nerves of 30 rabbits were resected, the free ends were anastomosed, and the effects of methylprednisolone and aminoguanidine on facial nerve regeneration were studied. The study showed that methylprednisolone had no beneficial effect in nerve regeneration, even increased degeneration [2,11,30].…”
Section: Discussionmentioning
confidence: 97%
“…Many different treatments have been described for the treatment of TPFNP, including aminoguanidine, melatonin, Vitamin E, and N-acetylcystein, due to their antioxidant and anti-inflammatory properties [2,29,30]. Therefore, agents with antioxidant and anti-inflammatory properties may help treat traumatic nerve palsy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, it is worth mentioning that Turgut et al have experimentally demonstrated in rats that melatonin prevents neuroma formation after transacting the sciatic nerve by enhancing axonal regeneration [118]. Recently, some studies have shown the positive effect of melatonin on preventing scar formation, increasing nerve regeneration and improving functional recovery [119,120]. However, the exact mechanisms by which melatonin limits fibrosis are currently unclear.…”
Section: Melatoninmentioning
confidence: 99%
“…44 These researchers compared the effects of aminoguanidine, MLT, and methylprednisolone; MLT supported regeneration after peripheral facial nerve neurorrhaphy. 45 Administrating MLT after stripping of the epineural vessels in a model of sciatic nerve injury supported axonal regeneration, reduced oxidative stress, and improved functional recovery. 46 More recently, Moretti et al demonstrated for the first time that MLT reduces injury to the blood-brain barrier after an excitotoxic insult and their results were supported by gene analyses.…”
Section: Current Studiesmentioning
confidence: 99%